2015
DOI: 10.1108/jm2-07-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on lot size with quantity discounts: 1995-2013

Abstract: Purpose – This paper aims to present a literature review on models developed for the economic order quantity (EOQ) problem with incremental and all-units discounts, extending the work of Benton and Park (1996) which covered the most significant literature, from 1963 to 1994, about EOQ with discounts and that has identified four open areas in this field of study. The modeling of lot size with discounts wishes to give good solutions for realistic situations, such as those concerning the discounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…The methodology applied in this work is based on the Webibliomining works proposed by Costa (2010), and also explored by Barros et al (2015) and Pereira and Costa (2015). More specifically, six steps are performed:…”
Section: Methodsmentioning
confidence: 99%
“…The methodology applied in this work is based on the Webibliomining works proposed by Costa (2010), and also explored by Barros et al (2015) and Pereira and Costa (2015). More specifically, six steps are performed:…”
Section: Methodsmentioning
confidence: 99%
“…The authors proposed a solution approach that generates stable coalition structures for the retailers taking into account the delay in payments and the discount quantity offered by the supplier. Through a simulation, the authors showed the effectiveness of their approach in solving large-scale problems and the effect of permissible delay in payments versus discount quantity on the coalition formation problem (Pereira and Costa, 2015).…”
Section: Jm2 151mentioning
confidence: 99%
“…This theory was developed by Harris (1913) but some years later become as a robust tool applied in many contexts. Many models have been developed modifying the basic formula or other approaches trying to reach more suitable solutions for real problems (Pereira and Costa, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%